Content Analysis of Tiktok @Ekidarehanf Social Media as a Means of Communication and Information Media - Indah Mardini Putri; Eka Fitri Qurniawati (Universitas Lambung Mangkurat, 2025)
In the current digital era, it has changed all the public's habits in using social media in all their activities, one of which is using the social media TikTok. Currently, TikTok users in Indonesia are firmly in second place in the world with 112.97 million users. And this is due to the public's need for information, whise the percentage level of the audience obtaining information through social media is 80.1%. Thisefore, this research aims to describe the content analysis of TikTok social media, which is not only used as a medium for entertainment, but is also used as a means of education for a wide audience. This research uses qualitative methods with a focus on content analysis on the social media content of the TikTok account @ekidarehanf which was published on January 1, 2023 - August 1, 2023. In addition, the grouping of published content is based on the Four Pillar Social Media Content Strategy. The research results show that the social media TikTok @ekidarehanf is a medium that publishes information and communication, which of the four pillars includes entertainment content, collaboration content, educational content and informational content. What Ekida publishes most on his TikTok account, namely @ekidarehanf, is educational content whise educational content is the main content published by Ekida as a young doctor.